Nursing Management of Avoiding Delayed Cerebral Ischemia (DCI) in SAH ruptured aneurysm patient post clipping and decompressive craniectomy: case study - Liya Alifah (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2023)
ABSTRACT Abstract: introduction. Cerebral aneurysm is dilatated of arterial vessel in the arterial circulation in the brain. Among 85% case of SAH caused by spontaneous ruptured aneurysm intracranial located in the cerebral artery. Subarachnoid hemorrhage causes of highly morbidity and mortality. Delayed Cerebral Ischemia (DCI) is complication of SAH and cause mortality and worst neurological outcome. DCI occure in 30% patient with SAH and undergo deficit motor, cognitive disfunction and decreases quality of life. Arterial vasospasm induce decreases blood flow progressively cause ischemia which is causes decreased of neurological function. Case presentation A 53-years-old man with SAH post clipping and decompressive craniectomy showed desaturated, bradycardia and hypotension postoperative clipping and decompressive craniectomy. Patient also had deficit neurological, decrease of motoric function and level of consciousness. Fisher modified scale and VASOGRADE scale showed patient have high risk of delayed cerebral ischemia. After 6 days in the NCCU patient showed increases of level of consciousness and motoric function, the result of TCD showed there is no occur of vasospasm. Discussion. The condition of decreases of level consciousness, motoric function indicated patient had damage of cerebral function and may occur DCI after clipping. The use management to avoid DCI such as maintain the blood pressure, oxygenation status, euvolemic and normoterm status is very important to improve cerebral blood flow. Nurse had an important role to observe, detection, critical thinking, providing intervention and coordinating to maintain this condition. Conclusion. SAH post clipping had high risk of complication DCI. Good teamwork among health worker in early detection and first aid improve the patient outcome.